2021 Changes in E/M Codes for Office-Based Practice: JPOSNA Coding Corner - Muchow, Ryan; Wiskerchen, Sarah (Journal of the Pediatric Orthopaedic Society of North America, 2021)
In this first installment of the JPOSNA Coding Corner, we hope to demystify the 2021 changes for an easier transition to the new coding requirements for E/M billing. Future JPOSNA Coding Corner topics will have a subspecialty focus on billing for different procedures. Beginning January 1, 2021, changes to the CPT guide-lines for new and established outpatient evaluation and management (E/M) codes take effect. Impacting codes in the ranges 99202-99215 (new and established office or other outpatient categories), the modifications will alter documentation requirements and will affect E/M code selection for pediatric orthopaedic surgeons.